CITED2 mutations potentially cause idiopathic premature ovarian failure (2012)
Anomalies in gonadal development in a mouse knockout model of Cited2 have been recently described. In Cited2 -/- female gonads, an ectopic cell migration was observed and the female program of sex determination was transiently delayed. We hypothesize that, in humans, this temporary inhibition of genes should be sufficient to provoke a developmental impairment of the female gonads, conducive to premature ovarian failure (POF). To establish whether CITED2 mutations are a common cause of the disease, we performed a mutational analysis of this gene in a panel of patients with POF and in a group of control women with normal fertility. We amplified and directly sequenced the complete open reading frame of CITED2 in 139 patients with POF and 290 controls. This study revealed 5 synonymous and 3 nonsynonymous variants. Among these, 7 are novel. The nonsynonymous variant c.604C and gt;A (p.Pro202Thr) was found uniquely in 1 woman from the POF group. In silico analysis of this mutation indicated a potential deleterious effect. We conclude that mutations in CITED2 may be involved in POF pathogenesis. © 2012 Mosby, Inc. All rights reserved.